2021
DOI: 10.1891/crnr-d-20-00032
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses ‘Assessment of Medical Errors

Abstract: PurposeThe aim of this study was to evaluate the quality of nursing students' assessment of cases of medical error.MethodThis descriptive cross-sectional study was conducted with 145 nursing students in İzmir, Turkey. The epidemiology of the medical errors that the students witnessed during clinical practice was examined. Then, the success of the students in using the Text-Based Medical Error cases tool developed by the researchers was examined.ResultsOf the students, 24.1% had witnessed medical errors during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies have shown that adverse events are closely related to patient safety and care quality, but about 50% of them can be prevented [ 38 , 39 ]. Because student nurses had poor clinical practice ability, weak critical thinking ability, a lack of communication skills, and an absence of teamwork awareness, they had become the “main force” leading to the occurrence of safety risks [ [40] , [41] , [42] ]. Our results showed that through the teaching-learning mode of CBL-SCT, student nurses in the experimental group significantly improved their practice skills in six nursing quality standards.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adverse events are closely related to patient safety and care quality, but about 50% of them can be prevented [ 38 , 39 ]. Because student nurses had poor clinical practice ability, weak critical thinking ability, a lack of communication skills, and an absence of teamwork awareness, they had become the “main force” leading to the occurrence of safety risks [ [40] , [41] , [42] ]. Our results showed that through the teaching-learning mode of CBL-SCT, student nurses in the experimental group significantly improved their practice skills in six nursing quality standards.…”
Section: Discussionmentioning
confidence: 99%